2004
DOI: 10.1083/jcb.200401150
|View full text |Cite|
|
Sign up to set email alerts
|

Endorepellin causes endothelial cell disassembly of actin cytoskeleton and focal adhesions through α2β1 integrin

Abstract: Endorepellin, the COOH-terminal domain of the heparan sulfate proteoglycan perlecan, inhibits several aspects of angiogenesis. We provide evidence for a novel biological axis that links a soluble fragment of perlecan protein core to the major cell surface receptor for collagen I, α2β1 integrin, and provide an initial investigation of the intracellular signaling events that lead to endorepellin antiangiogenic activity. The interaction between endorepellin and α2β1 integrin triggers a unique signaling pathway th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
215
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 230 publications
(224 citation statements)
references
References 47 publications
7
215
0
2
Order By: Relevance
“…3C). This provides a molecular explanation for the lack of LG3 affinity to heparin and for the lack of requirement for cell surface heparan sulfate for full biological activity (15). Moreover, electrostatic analysis indicated that the predicted Ca 2ϩ -coordinating region forms an acidic pocket on the surface, despite variations in nearby loop regions.…”
Section: Three-dimensional Molecular Model Of Endorepellin Lg3mentioning
confidence: 98%
See 3 more Smart Citations
“…3C). This provides a molecular explanation for the lack of LG3 affinity to heparin and for the lack of requirement for cell surface heparan sulfate for full biological activity (15). Moreover, electrostatic analysis indicated that the predicted Ca 2ϩ -coordinating region forms an acidic pocket on the surface, despite variations in nearby loop regions.…”
Section: Three-dimensional Molecular Model Of Endorepellin Lg3mentioning
confidence: 98%
“…N-terminal sequences were determined by automated Edman degradation at the Harvard University Microchemistry Facility. Preparation of adenovirus-endorepellin (Ad-ER) and transduction experiments were performed as described previously (15).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work by our group and others demonstrated that EC apoptosis represents a previously unrecognized pathway contributing to ECM proteolysis (5,6,18,19,43,44). We showed that in EC, apoptosis triggers endorepellin proteolysis and LG3 release, which interacts with ␣2␤1 integrins on EC, platelets, and fibroblasts, and triggers angiostatic, thrombogenic, and anti-apoptotic responses (20,(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%